The effect of the Hartz reform on unemployment duration and post-unemployment outcomes. A difference-in-differences approach - Amable, Bruno; Françon, Baptiste (Paris, 2014)
"In this paper, we investigate the microeconomic effects of one major feature of the German Hartz Reforms (2003-2005), namely the reduction in compensation duration for older unemployed above 45 years of age. We look at two potential effects of this measure: on job take-up rates, but also on post-unemployment outcomes, through various indicators of matching quality (job stability, skill adequacy) and job quality (type of job contract). Applying difference-in-differences estimators, we show that the effects of this specific feature were rather scant. Regarding unemployment duration, only unemployed within a specific age group (55 to 59 years old) were affected by the reform. Evidence suggests that this is because they previously used unemployment schemes as a bridge to early retirement. In addition, there is some evidence of detrimental effects on job or matching quality."